TEKNIS-EKONOMIS PADI SAWAH IRIGASI UNTUK PENINGKATAN PENDAPATAN PETANI DI KABUPATEN NABIRE PAPUA - Afrizal Malik (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
Aim of this assessment is to study the behavior of farmers in the application of  technology  and  to  analyze  irrigated  rice  paddy  both  input  and  output.  Studies carried  out  in the  center  of irrigated  lowland  rice  in  Nabire,  were  doing  the  paddy rice  farm  implement  at  least  two  years.  Primary  data  collection  random proportionally  in  the  form  of  a  survey  using  questionnaires  in  April  2015  from  the results of paddy rice cultivation MH (October/November 2014 and January/February 2015)  as  many  as  43  farmers  as  respondents.  Primary  data  includes  cultivation technology,  inputs  and  outputs.  All  data  were  tabulated  and  interprestation.  Data were analyze in descriptive and quantitive way. The result showed that responses of farmers in this area depend on how the technology can improve paddy’s productivity and  the  farmers  income.  The  dynamics  of  the  response  of  farmers  to  increase productivity  technology  is  relatively  stable,  especially  in  components  commonly applied  to  farmers  in  the  cultivation  of  paddy  (how  is  the  tillage,  weeding  and fertilizer application). Technology components that are sensitive to productivity and affect  the  income  of  such  varieties  and  fertilizers  used  almost  similar  to recommendation. Productivity produced 4.92 tonnes / ha dry milled grain with a profit rate of  Rp 11,588,600  million (B/C 1.89).  Furthermore, it is necessary to study  about the use of fertilizer, because fertilizer recommendation just based on Phoska forecasts.Moreover,  there  must  be  effort  to  convince  farmers  to  use  Legowo  technique  to improve  paddy’s  productivity.  Scarcity  of  labor  at  planting  and  harvest  need  to  be think in the future and also dissemination agricultural tools like (rice transplanter and a harvester/combine haevester) needs to be disseminated for farmers and stakeholders there.